Water extract of green tea old leaves as a metal corrosion inhibitor. - Que, Le Xuan; Thu, Luc Van (Vietnam Journal of Chemistry, 2012)
Corrosion inhibitors original from natural products have been considered preferential due to the environment friendly effect. Green tea is an especially tropical produce in Vietnam, which is very rich of the polyphenol compounds. In our study, water extracts of Thainguyen green tea old leaves were studied as a corrosion inhibitor in acid solutions. Firstly the old tea leaves were extracted in boiled water. The extract then was thermally boiled down to prepare tea glues. The tea leaf extracts and glues were then dissolved at different concentrations in 2 M H2SO4 solution. The corrosion inhibition of the extract and glues on the mild steel (construction steel) has been studied using electrochemical polarization and impedance technique. The obtained results of icor measurements, Tafel slopes and Rct analyses, inhibition efficiency calculation… show that the water extract and glues of Thainguyen green tea old leaves manifest good corrosion inhibitors, with an efficiency up to more than 90%. The corrosion inhibitors affect both anodic and cathodic reactions. The mechanism of inhibition is an adsorption of the polyphenol compounds on the metal surface in both anodic and cathodic branches.